Integrasi Nilai-nilai Kecerdasan Emosional Perspektif Daniel Goleman dalam Al-Qur’an - Uliyatul Marfu'ah (MA'ALIM: Jurnal Pendidikan Islam, 2024)
The purpose of this study, first, is to find out the values of emotional intelligence perspective of Daniel Goleman. Second, to know the integration of the values of emotional intelligence perspective of Daniel Goleman in the Qur'an. This type of research is literature research. Data are taken from various scientific literature sources such as books, journals, and various types of scientific papers relevant to research studies. Data collection techniques use documentation techniques, then analyzed with content analysis methods. The results of this study are: emotional intelligence according to Daniel Goleman includes five aspects, namely self-awareness, self-regulation, motivation, empathy and social skills. These five aspects cannot be possessed suddenly, but require a process in learning them and the environment has a great influence in shaping emotional intelligence. The Qur'an discusses these five aspects in detail and thoroughly as a guide for Muslims to guide them in living their daily lives. First, the aspect of self-awareness (QS. An-Nisaa: 1, QS. Al-Hashr: 18). Second, the aspect of self-regulation (QS. Ar-Rad: 28). Third, the motivation aspect (QS. Adz-Dzaariyat: 56, QS. Al-An'aam: 162, QS. Ar-Ra'd: 11, QS. Al-Qashash: 77, QS. Al-Maidah: 48). Fourth, the aspect of empathy (QS. Al-Balad: 17, QS. Maryam: 96, QS. An-Nisaa': 1). Fifth, aspects of social skills (QS. Al-Maa'idah: 2, QS. Ali-Imran: 103, QS. An-Nisaa: 59, QS. An-Nisa: 114).